2017
DOI: 10.1111/1745-9125.12160
|View full text |Cite
|
Sign up to set email alerts
|

Age, Period, and Cohort Effects on Death Penalty Attitudes in the United States, 1974–2014

Abstract: In this article, we further the understanding of both changes in public opinion on capital punishment in the United States and changes in the factors associated with public opinion on the death penalty. Support for the death penalty may be motivated by events happening during specific time periods, and it can vary across birth cohorts as a result of cohort‐specific socialization processes, demographic changes, and formative events that are specific to each generation. An explication of the sources of and varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 96 publications
(164 reference statements)
4
46
0
Order By: Relevance
“…I evaluate external validity by first comparing my estimates to national, state-level, over-time, and individual-level measures of punitive sentiment provided in prior studies, and then comparing the MRP estimates to state polling data. Consistent with prior studies (Anderson et al 2017;Ramirez 2013;Shi et al 2020), punitive policy support among the black and white publics exhibit similar over-time trends, rising in the 1970s and 1980s before ultimately declining after 1990 (see Figure 2). The over-time patterns are also consistent with Enns's (2014) reports of national punitive policy support, where punitiveness peaks in the mid-1980s and 1990s before declining.…”
Section: Validity Checkssupporting
confidence: 86%
See 1 more Smart Citation
“…I evaluate external validity by first comparing my estimates to national, state-level, over-time, and individual-level measures of punitive sentiment provided in prior studies, and then comparing the MRP estimates to state polling data. Consistent with prior studies (Anderson et al 2017;Ramirez 2013;Shi et al 2020), punitive policy support among the black and white publics exhibit similar over-time trends, rising in the 1970s and 1980s before ultimately declining after 1990 (see Figure 2). The over-time patterns are also consistent with Enns's (2014) reports of national punitive policy support, where punitiveness peaks in the mid-1980s and 1990s before declining.…”
Section: Validity Checkssupporting
confidence: 86%
“…Fortner (2015:9) forcefully made this case in reviewing New York's Rockefeller Drug Laws; he argues that "[a]fter tilting the discursive terrain in the direction of racial equality during the struggles of the civil rights movement, working-and middle-class African Americans tilted it in favor of punitive crime policies" (see also Foreman 2017). Indeed, public opinion research shows that punitive sentiment among white and black populations exhibited "parallel trends," with their support for tough crime policy rising and falling in tandem for both racial groups during mass incarceration (Anderson, Lytle, and Schwadel 2017;Ramirez 2013;Shi, Lu, and Pickett 2020).…”
Section: Who Controls the Law?mentioning
confidence: 99%
“…There were no significant differences across groups in either year for worry about crime, confidence in the criminal justice system, Catholic, and crime victim. Demographically in both years, death penalty supporters were least likely to live in an urban setting, more likely to be male, had the lowest prevalence of a bachelor’s degree, and had the highest score on conservativism (Anderson et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Due to measurement limitations and theoretical inattention, little is known about who the unsures are and how they may differ from those respondents who have clearer opinions. Demographically, death penalty supporters, compared to non-supporters, tend to be men, White, older, and politically conservative (Anderson et al., 2017; Pew Research Center, 2015). Research has explored several factors contribute to individual attitudes about the death penalty and punitive sentiment more generally; as noted, such research typically excludes the unsures.…”
Section: Public Support For the Death Penaltymentioning
confidence: 99%
“…In research on observer reactions, previous studies have examined participant characteristics and indicated that participant sociodemographic characteristics, including gender, ethnicity, age, and religiosity, are associated with their attitudes toward capital punishment. Men tend to express stronger support for capital punishment than women (e.g., Adinkrah & Clemens, 2018;Anderson et al, 2017;Godcharles et al, 2019). Ethnic minorities tend to oppose the death penalty more than ethnic majorities (Peshkopia & Stephen Voss, 2016;Unnever et al, 2008;Vollum & Buffington-Vollum, 2010).…”
Section: Observer Characteristicsmentioning
confidence: 99%